Node Classification Based on Functionality in Energy-Efficient and Reliable Wireless Sensor Networks - Ning Sun; Youngbuk Cho; Sangho Lee (International Journal of Distributed Sensor Networks)
Energy efficiency and reliability are two important factors when we design a wireless sensor network (WSN). In this paper, we proposed an energy-efficient and reliable hierarchical mechanism for WSNs. We utilized clustering structure to decrease energy consumption. Because cluster head plays an important role in WSN, we designed a substitute of cluster head (SCH) in order to guarantee the data propagation reliability. Based on different functionalities of sensor nodes we creatively classify sensor nodes into five categories: branch node (BN), cluster head (CH), substitute of cluster head (SCH), intermedium node (IN), and normal node. By adopting different MAC and network strategies for different node categories, energy consumption can be greatly reduced and data reliability can be significantly increased in the proposed WSN mechanism. The simulation results showed that this proposed mechanism realized the objective in aspects of energy efficiency and reliability.